Prevalence of Dry Eye Disease in an Urban Community - Kevin Matthew Serafin B. Panggat, MD; Rainier Victor Covar, MD; Ruben Lim Bon Siong, MD (Philippine Journal of Ophthalmology)
Objective: To determine the prevalence of dry eye disease in an urban community in the Philippines.